School Desegregation : Oral Histories toward Understanding the Effects of White Domination - Noblit, George W.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2015)
This book is written for the Millennial Generation to educate them about what school desegregation was actually about$1 (Bthe struggle over white domination in the United States. The textbooks they read as high school students describe the heroic efforts of African Americans to achieve civil rights but do not describe who was denying them these rights$1 (Bwhite Americans. The oral histories in this book reveal how individuals navigated efforts to achieve educational equity amidst efforts to reassert white domination. These accounts counter the textbook history the Millennial Generation read which omits the massive white resistance to school desegregation, the various ways whites used subterfuge to slow down and redirect school desegregation in what would more benefit whites, and the concerted white political backlash that has been ensconced in educational policy and reform beginning with A Nation at Risk and continuing in No Child Left Behind. That is, educational policy as we know it is all about asserting white domination and not about educating children, and thus the Millennial Generation is faced with undoing what their parents and grandparents have done.s
Keywords: Education; Education; Education, general